Discrete modeling and experimental validation of the model of a cantilever flexible beam - Silva, Antônio Carlos de Assis; Gonçalves, João Bosco; Soares, Álvaro Manoel de Souza [UNESP] (Praise Worthy Prize, 2015)
Cantilevered beams are studied in many ways because they are simple and largely applicable in many engineering problems. This study shows the development of a discrete dynamic model for a flexible cantilever beam and the experimental model validation. The model of the flexible beam was obtained by the Lagrangian formalism and its discretization was performed using the concentrate elements technique. An experiment where a cantilever beam was excited by a white noise was set up, with a capacitive accelerometer in the free end of the beam. Data acquisition was carried out using the software LabVIEW®, developed by National Instruments. In order to improve experimental data, the beam Young's modulus was experimentally determined. The final results show a good agreement between the experimental data and the analytical model.
Keywords: Cantilevered beam; Experimental data acquisition; Labview